Photoreflectance study of Al0.45Ga0.55As/GaAs superlattice: optical transitions at the miniband Γ and Π points - Motyka, Marcin; Sęk, Grzegorz; Janiak, Filip; Ryczko, Krzysztof; Misiewicz, Jan; Kosiel, Kamil; Bugajski, Maciej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, we present the results of photoreflectance (PR) investigation of an Al0.45Ga0.55As/GaAs superlattice (SL). The modulation spectra have revealed a number of features at both room and low temperature (10 K) which could be associated with the optical transitions between the minibands of the superlattice. Based on calculations within the effective mass approximation they have been identified as transitions between the miniband edges, i.e., the so-called Γ and Π points, respectively, including the high index transitions and those related to the light holes. Tuning the structure parameters around the nominal ones treated as semi-free in the theoretical considerations allowed the growth accuracy of such a complex system to be verified.
Optica Applicata, Vol. 39, 2009, nr 4, s. 897-902
Keywords: optyka; superlattice; photoreflectance; modulation spectroscopy